All just grandiose plans and talk: The destruction of Oswald Pirow’s reputation as Minister of Defence, 1940 - Mouton, Frances Alexander (Scientia Militaria - South African Journal of Military Studies, 2020)
The popular perception of Oswald Pirow is that of an incompetent Minister of Defence, much derided for his bush carts pulled by oxen in the era of the blitzkrieg doctrine of dive-bombers and tanks. However, this was not the perception of him in the years between 1933 and 1939. When Pirow became Minister of Defence in 1933, the Union Defence Force was in a poor state. During the Great Depression between 1929 and 1933, austerity measures had reduced the already small army to an insignificant force. In what has been described as a Pirowian renaissance he succeeded in improving the preparedness of the Union Defence Force drastically. Ian van der Waag points out that with the outbreak of the Second World War, South African defences were in a better state of preparation than during any other period in its peacetime history. This was a considerable achievement, as Pirow had to deal with the vehement hostility of the National Party who viewed the Union Defence Force as a tool to serve British imperialism. In addition, the average white voter was extremely reluctant to pay taxes to fund a standing army, while the rise of Nazi Germany made it near impossible to secure modern armaments from Britain. What ultimately destroyed Pirow’s reputation as Minister of Defence was his disastrous performance in the 1940 parliamentary session. His vindictive attacks on Jan Smuts made it possible for the premier to launch a devastating counterattack, condemning him as a fraud and an incompetent windbag. In the process, Smuts succeeded in destroying Pirow’s reputation as a highly regarded administrator and as a potential prime minister.